The Role Of A Decision Support System In Enhancing The Management Of Sexual Violence Cases In Higher Education Using The Saw Method Through An Android-Based Application - Wahyuni, Elyza Gustri; Wahyudi, Rian Tri; Fadhillah, Lalam Fathonah (Jurnal Teknik Informatika (Jutif), 2025)
The rising prevalence of sexual violence in higher education institutions demands urgent attention, highlighting the need for an efficient and responsive reporting system. Android-based applications for reporting sexual violence play a vital role in addressing this issue. This research proposes an application designed to provide ease of access and usability, enabling victims or witnesses to promptly submit reports supported by video, audio, and real-time GPS data. Such empirical evidence increases the likelihood of successful follow-up actions and strengthens legal claims against perpetrators. Timely responses are especially critical for the Sexual Violence Prevention and Handling Task Force (PPKS) to mobilize campus security teams effectively and reduce long-term trauma experienced by victims. An integral component of the application is a Decision Support System (DSS) that utilizes the Simple Additive Weighting (SAW) method to assess the severity of reported cases—categorized into mild, moderate, or severe. This system facilitates faster and more accurate decision-making during the investigation and handling phases. Functional and case testing resulted in 100% success, aligning perfectly with manual calculations and real-world scenarios. The urgency of this research lies in the pressing need for a reporting system that is not only reactive but also proactive in preventing sexual violence. The application demonstrates strong potential to support systemic reform in campus reporting mechanisms, enhance victim trust in reporting processes, and shift the paradigm from reactive intervention to preventive action. Ultimately, this research contributes to building a safer, more responsive, and survivor-centered campus environment.